Natural yeast flora of different varieties of grapes used for wine making in India - Chavan, Pradnya; Mane, Sarika; Kulkarni, Girish; Shaikh, Shamim; Ghormade, Vandana; Nerkar, Devidas P.; Shouche, Yogesh; Deshpande, Mukund V. (Food Microbiology, 2009)
The natural Saccharomyces and non-Saccharomyces yeast flora present on the grape berries significantly affect wine production. Six grape varieties, Bangalore blue, Zinfandel, Cabernet, Chenin Blanc, Sauvignon Blanc and Shiraz are being used in India for wine making. The yeast diversity was studied on the basis of morphological, colony, physiological characteristics and 5.8S-ITS sequencing of rDNA of the isolates. Eleven different species belonging to seven genera were identified as: Candida azyma, Candida quercitrusa, Debaryomyces hansenii, Hanseniaspora guilliermondii, Hanseniaspora viniae, Hanseniaspora uvarum. Issatchenkia orientalis, Issatchenkia terricola, Pichia membranifaciens, Saccharomyces cerevisiae and Zygoascus steatolyticus. H. guilliermondii was the predominant species while S. cerevisiae was observed occasionally in the six vine varieties. For the first time, C. azyma was isolated from Bangalore blue and Cabernet varieties grown in different localities. This association may be attributed to the change in cropping pattern from sugarcane to viticulture in the vine growing regions and the known association of C. azyma with sugarcane phylloplane. Further analysis of the indigenous strains and the qualitative and quantitative changes in the flora during fermentation will be useful to understand wine quality and to design preservation strategies to control wine spoilage. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: 5.8S-ITS sequence; Identification; Physiological; Wine yeasts

Zinc inhibits glycation induced structural, functional modifications in albumin and protects erythrocytes from glycated albumin toxicity - Tupe, Rashmi; Kulkarni, Amruta; Adeshara, Krishna; Sankhe, Neena; Shaikh, Shamim; Dalai, Sayli; Bhosale, Siddharth H.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2015)
The present work aims to investigate the concentration and time dependant effect of zinc on the in vitro non enzymatic modifications of albumin by diabetic levels of glucose. Further, preventive and curative effect of zinc was studied by adding zinc before and after initiation of glycation respectively. Glycation of albumin was done at different concentrations of zinc (125, 250 and 500 mu M) at different time intervals (21,28 and 35 days) with appropriate controls. The antiglycation potential of zinc was assessed by estimating different markers of albumin glycation (fructosamines, carbonyls, bound sugar, AGEs), structural modifications (free amino, thiol group, beta amyloid, native PAGE, ANS binding, fluorescence lifetime decay and CD analysis) and functional properties (antioxidant activity, hemolysis). Zinc at highest concentration (500 mu M) significantly reduced modifications of albumin which was comparable to aminoguanidine and also protected secondary and tertiary structure of albumin after 28 days of incubation. Zinc exhibited significant protective effect on erythrocytes by inhibiting hemolysis. Thus the present study indicate preventive mode of albumin glycation inhibition by zinc. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Albumin; Erythrocytes; Glycation